2022
DOI: 10.1177/18632521221080478
|View full text |Cite
|
Sign up to set email alerts
|

Are early antero-posterior and lateral radiographs predictive of clubfoot relapse requiring surgical intervention in children treated by Ponseti method?

Abstract: Purpose: To investigate the value of antero-posterior and lateral radiographs in predicting clubfoot relapse after treatment with the Ponseti method. Methods: This was a retrospective review of 104 children (157 feet) younger than 3 months of age with idiopathic clubfoot treated using the Ponseti method at our institution between January 2007 and December 2014. All patients underwent Achilles tenotomy and were divided into two groups according to the need for further surgery to correct the deformity: relapsed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In addition, the measurement method used in the study was shown to have good intraand inter-observer reliability. 1,7 The clubfeet included in this study were corrected by initial treatment. A moderate midfoot break may be due to the fact that radiographs were performed with the patient awake, whose foot was held by an adult (Figure 4; B1); Figure 4 (B2) shows a more severe midfoot break.…”
Section: Radiographic Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the measurement method used in the study was shown to have good intraand inter-observer reliability. 1,7 The clubfeet included in this study were corrected by initial treatment. A moderate midfoot break may be due to the fact that radiographs were performed with the patient awake, whose foot was held by an adult (Figure 4; B1); Figure 4 (B2) shows a more severe midfoot break.…”
Section: Radiographic Measurementsmentioning
confidence: 99%
“…5 , 6 The deformities we found to be most frequently involved in recurrence were cavus and dynamic supination. 1 …”
Section: Relapsementioning
confidence: 99%
See 2 more Smart Citations
“…We read with great interest the article by Li et al entitled “Are early antero-posterior and lateral radiographs predictive of clubfoot relapse requiring surgical intervention in children treated by Ponseti method?.” 1 We congratulate the authors on their retrospective analysis study to evaluate the role of radiographs in predicting relapse following clubfoot correction by Ponseti’s method. We had an extensive discussion on this article in our institutional journal club, which yielded the following observations and requires clarification on the following concerns:…”
mentioning
confidence: 99%